Using Real World Evidence to Describe Pulmonary Arterial Hypertension Treatment Patterns, Healthcare Resource Utilization, and Costs Associated with PDE-5 Inhibitor Monotherapy - George Ruiz; Jason Yeaw; Cassandra A. Lickert; Ajita P. De; Rolin L. Wade; Janis Pruett; William Drake (Journal of Health Economics and Outcomes Research, 2018)
**Background:** Pulmonary arterial hypertension (PAH) is described by proliferation of small pulmonary arteries leading to increased pulmonary vascular resistance, right ventricular failure, and death. Research confirms long-term improvement in composite morbidity and mortality endpoints on some endothelin receptor antagonists alone and in combination with phosphodiesterase type 5 inhibitors (PDE-5is) but not with PDE-5i monotherapy. While current treatment guidelines incorporate these findings, a substantial number of patients are started or maintained on PDE-5i monotherapy.